ANALISIS PEMASARAN JAMBU METE DI KABUPATEN WONOGIRI - Setyowati, Setyowati (Universitas Sebelas Maret, 2004)
The aims of the study are; (1) to know farmer's sahre of cashew nut's marketing profil in Wonogiri district and (2) to know the efficiency of cashew nut's marketing profil in Wonogiri district. The study is a case study in Ngadirojo sub district of Wonogiri district. The sampling method used in the study are purpossive sampling. the sample consist of the 80 smaples, which is classified into two groups.